Evaporative Cooling Heat Transfer of Water From Hierarchically Porous Aluminum Coating. Issue 5 (16th March 2018) - Fathi, Nabeel; Kim, Jinsub; Jun, Seongchul; King, Ryan M.; Amaya, Miguel; You, Seung M.
ABSTRACT: A study of evaporative cooling of water was conducted using dual-scale hierarchically porous aluminum coating. The coating was created by brazing aluminum powders to a flat aluminum plate. The effects of particle size and thickness on evaporative heat transfer were investigated using average aluminum particle diameters of 27, 70, and 114 µm and average coating thicknesses of 560, 720, and 1200 µm. Constant ambient temperature of 24°C and relative humidity of 50% were provided throughout the study. Evaporative cooling tests on the coated surfaces were compared to the plain surface. Tested dual-scale porous coatings enhanced evaporative heat transfer significantly, compared to that of the plain surface, due to the effective wicking of water to the entire heated area. With particle size increase, both the wickability and dryout heat flux were significantly increased. The dryout heat flux with the particle size of 114 µm was 3.2 times higher than that with the particle size of 27 µm. At the fixed particle size of 70 µm the dryout heat flux increased as thickness increased, which resulted in the maximum dryout heat flux of 10.6 kW/m 2 and the maximum heat transfer coefficient of 251 W/m 2 K at the coating thickness of 1200 µm.